Connectivity on fixed air route in aeronautical ad hoc networks - Chang-yuan LUO; Yu-long SONG; Zhan-zhan GAO (Tongxin xuebao)
Connectivity is the premise and foundation of networking and routing.Researches on fixed air route connec-tivity in aeronautical ad hoc networks are inadequate at present.Aiming at this situation,a method of connectivity re-searching was introduced.By combining characteristics of realistic layered with two-way air routes,and building the air-craft distribution as well as flight route models,the method deduced a math expression of one-dimensional route connec-tivity.Based on the above,probability figure was used to study on the network connectivity in view of probability matrix,and the correctness of the results were proved by experiments.Then,according to the practical flight data,the connec-tivity of one-dimensional route and network in Chinese partial airspaces was simulated; indicating that aeronautical ad hoc networks in the mentioned airspaces are feasible.Finally,some reasonable advises are given to improve the connec-tivity in four aspects,such as flight arrangement,planning and so on.